The Association of Neonatal Stunting Undernutrition With Early Childhood Dental Caries - Dewa Made Wedagama; I Gusti Ayu Ari Agung; Ilma Yudistian; Ni Putu Idaryati; I Gusti Agung Ayu Hartini; Ni Putu Widani Astuti; Dewi Farida Nurlitasari (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Early childhood dental caries (ECDC) is a major public health problem affecting up to 90% of children worldwide and is related to diet and nutrition.  Early childhood undernutrition, including fetal stunting, and stunting, is a global problem.  Undernutrition in neonatal stunting could be the cause associated with ECDC.  This scoping-review aims to understand the linkage mechanism behind neonatal stunting undernutrition to ECDC. This concept is expected to generate further research to help prevent both growth,   stunting undernutrition and ECDC. Review:  This study uses the PRISMA method, with the steps: (1) Question framework (literature study); (2) Search for articles in databases (on PubMed, ProQuest, Google Scholar), and journal data bases with articles published from 2017 to 2024; (3) Selection of relevant research; (4) Data extraction; (5) Synthesis with narrative method. The study obtained 5 articles to be reviewed, proving that pregnant women who experience chronic undernutrition (mainly deficiency of protein, vitamins A, B, C, D, E, minerals Fe, Ca, P and Zn), will contribute to giving birth to undernutrition stunting neonatal, with severe ECDC in 1 article; 1 articles analyzing the strong relationship between chronic neonatal stunting undernutrition with enamel hypoplasia, low quality and rate of saliva, an important cause of ECDC; and 3 article analyzing the neonatal stunting undernutrition is associated with severe ECDC. Conclusion:  Chronic undernutrition in pregnant women and subsequent neonatal stunting significantly contribute to the risk of severe ECDC.